Aseptic Meningitis Caused by Coxiella Burnetii - Figueiredo, C (2017)
Acute Q fever can have multiple presentations but neurologic involvement is rare. We describe the case of a 16-year-old female with severe headache and aseptic meningitis with acute Coxiella burnetii infection.